Varieties of Monetary Reforms - Siklos, Pierre (IMF Working Papers; Working Paper, 1994)
This paper surveys three types of monetary arrangements. It considers how the choice of an exchange rate regime, the degree of central bank independence, or choice of currency unions or boards depends not only on economic considerations but also on political economy considerations. In economic terms, the choice of monetary regime will depend on the policy that is best suited to reducing or stabilizing inflation. In political economy terms, the choice of monetary arrangement will ultimately depend on how independent a country wishes to be from shocks emanating from the rest of the world and the weight politicians attach to influencing economic conditions in their own country.